Factors Associated with Placental Vascularization Measured by 3D Power Doppler Ultrasonographic Sphere Biopsy between 11 and 14 Weeks of Gestation - Demers, Suzanne; Boutin, Amelie; Dembickaja, Regina; Campanero, Mercedes; Nicolaides, Kypros (American Journal of Perinatology, 2018)
Objective Preeclampsia is associated with placental vascularization disorders. Ultrasonographic sphere biopsy (USSB) of the placenta can estimate the vascularization of the placenta and potentially the risk of preeclampsia. We aimed to explore the factors related to placental vascularization measured with USSB in the first trimester.Study Design A prospective cohort was conducted in women recruited at 11 to 14 weeks. Three-dimensional acquisition of the placenta with power Doppler was undertaken along with crown-rump length (CRL). Using USSB of the full placental thickness at its center, vascularization index, flow index, and vascular flow index were measured. Pearson's correlation coefficients and multivariate linear regression were used to correlate the vascularization indices with CRL and maternal characteristics.Results A total of 5,612 women were recruited at a mean gestational age of 12.8 ± 0.6 weeks. We observed that vascularization indices increase with CRL. After adjustment, we observed that maternal age, ethnicity other than Caucasian, and body mass index were associated with lower vascularization indices, while diabetes, smoking, and assisted reproduction technology were not. We observed that parous women without history of preeclampsia had greater vascularization indices compared with nulliparous women.Conclusion Placental vascularization indices assessed by USSB fluctuate with gestational age, ethnicity, maternal age, body mass index, and previous pregnancy history.
Keywords: pregnancy; preeclampsia; placenta; ultrasound; Doppler